Drought activates MYB41 orthologs and induces suberization of grapevine fine roots - Zhang, Li; Merlin, Isabelle; Pascal, Stéphanie; Bert, Pierre‐François; Domergue, Frédéric; Gambetta, Gregory A. (Plant direct, 2020)
The permeability of roots to water and nutrients is controlled through a variety of mechanisms and one of the most conspicuous is the presence of the Casparian strips and suberin lamellae. Roots actively regulate the creation of these structures developmentally, along the length of the root, and in response to the environment, including drought. In the current study, we characterized the suberin composition along the length of grapevine fine roots during development and in response to water deficit, and in the same root systems we quantified changes in expression of suberin biosynthesis‐ and deposition‐related gene families (via RNAseq) allowing the identification of drought‐responsive suberin‐related genes. Grapevine suberin composition did not differ between primary and lateral roots, and was similar to that of other species. Under water deficit there was a global upregulation of suberin biosynthesis which resulted in an increase of suberin specific monomers, but without changes in their relative abundances, and this upregulation took place across all the developmental stages of fine roots. These changes corresponded to the upregulation of numerous suberin biosynthesis‐ and export‐related genes which included orthologs of the previously characterized AtMYB41 transcriptional factor. Functional validation of two grapevine MYB41 orthologs, VriMYB41 and VriMYB41‐like, confirmed their ability to globally upregulate suberin biosynthesis, export, and deposition. This study provides a detailed characterization of the developmental and water deficit induced suberization of grapevine fine roots and identifies important orthologs responsible for suberin biosynthesis, export, and its regulation in grape.